ANALISIS PROFITABILITAS DAN EFISIENSI OPERASIONAL PADA KSP KOPDIT SUBE HUTER - Tius, Angelbert Faridzal; Mitan , Wilhelmina; Lamawitak , Paulus Libu (Jurnal Projemen UNIPA, 2025)
This study aims to analyze the profitability and operational efficiency of Sube Huter credit union. Profitability is measured by the Net Profit Margin (NPM) ratio, while operational efficiency is measured using the Operating Cost to Operating Income ratio and several other indicators related to operational costs. The data utilized in this research consist of secondary data from Sube Huter's credit union financial reports for the period 2020 to 2024. The analysis was conducted employing the financial ratio method to assess the cooperative's profitability and operational efficiency. The results indicate that the cooperative's profitability falls into the unhealthy category with a consistent NPM of 2%, while operational efficiency is categorized as less healthy with a Operating Costs to Operating Income value approaching 97-98%. The primary cause of low efficiency is high operational costs, particularly employee salary expenses that are not commensurate with revenue. However, the indicator of operating costs to total receivables still demonstrates healthy performance. This study recommends the implementation of more effective cost management, financial product development, and increased transaction volume to enhance the cooperative's profitability and operational efficiency.